Too Small to Regulate - Basu, Kaushik; Dixit, Avinash (World Bank, Washington, DC, 2014)
The paper argues that to achieve compliance of firms with regulations such as product quality or environmental or health standards it is better to have industries with a few large corporations than numerous small firms. A model is constructed to show that limited liability constraints bind more easily in competitive industries, making it harder to impose sufficiently severe penalties and costlier to send sufficient monitors. Having large corporations allows the government effectively to delegate some of its monitoring functions to the managers of the corporation. The tradeoff between this issue and the usual argument in favor of competition is considered.